Analisis dan Perancangan Sistem Kriptografi Merkle-Hellman Knapsack Untuk Mengamankan File Text - Budiman, Arief; Sari, Yunita (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Cryptography is a field that is really needed in the current era of globalization where security and confidentiality of information are very difficult to maintain considering wide and open communication access. Cryptography currently has a variety of methods and techniques which are divided into two categories, namely symmetric cryptography and asymmetric cryptography where their use depends on needs and conditions. The Merkle Hellman Knapsack method is an asymmetric cryptography method that uses a public key and a private key so that tapping and cracking becomes more difficult due to the use of different keys both during encryption and during decryption. Application development using the Merkle Hellman Knapsack method generates public keys and private keys using super increasing and inverse modulo series values, making the cryptanalysis process more difficult. The system developed is able to provide an alternative in securing text data.